Analysis of partially composite foam insulated concrete sandwich structures. (15th May 2015) - Bai, Fengtao; Davidson, James S.
Highlights: Absence of reliable analysis methodology for Sandwich Panel is addressed. A Discrete Model is developed and shown to improve accuracy. Behavior is generally classified as flexural and shear components. Upper and lower bounds of deflection, end slip and internal forces are derived. Abstract: This paper presents the theoretical development that defines the small displacement behavior of foam insulated concrete sandwich panels. Composite theories presented by other researchers are first thoroughly reviewed and scrutinized in the context of their use for precast concrete beams. A more rigorous Discrete Model that incorporates the complex shear deformation behaviors and independent flexural resistance of the concrete wythes is then derived. Experimental data from full-scale precast sandwich panel tests are used to validate the developed methodology. Finally, it is demonstrated that this study provides a rigorous analysis methodology for foam insulated concrete sandwich structures.